Information System Design for Monitoring and Evaluation of Learning on Blended Learning - Nurliana Nasution; Yuvi Darmayunata; Sri Wahyuni (AL-ISHLAH: Jurnal Pendidikan, 2022)
The Pandemic Covid-19 necessitates all activities to be network-based, including the collegiate learning process. Prior to the epidemic, instructors were mechanically or face-to-face evaluated for their learning. Monitoring and evaluation, on the other hand, are carried out online during the e-learning learning process. However, in the learning process through e-learning, monitoring and evaluation are carried out online. To facilitate the monitoring and evaluation of online learning by lecturers, it is necessary to build a web-based information system. The purpose of the research is the creation of an information system for monitoring and evaluating learning evaluation through blended learning. The research methodology used is a research and development research design using waterfall analysis with the stages of requirements analysis, system design, implementation, integration and testing, operation and maintenance. The object-oriented research target is the monitoring and evaluation assessment information system. The result of the research is the development of an application for monitoring and evaluating learning assessments there are: (1) Using the system, the monitoring and evaluation of learning carried out by the monitoring and evaluation team can be easily carried out during the evaluation process. (2) The system can display a description of the results of the evaluation of learning monitoring and evaluation, (3) The system developed is used at the college for monitoring and evaluating learning activities through blended learning.